2017
DOI: 10.1111/vcp.12513
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic and plasma chemistry RIs for cultured Striped catfish (Pangasius hypophthalmus) in recirculating aquaculture systems

Abstract: Reference intervals reported here can help veterinarians and fish health specialists monitor the health status of Striped catfish under recirculating aquaculture conditions for research, exhibition, and production purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Varsamos et al (2005) reported that the osmolality in fish is not regulated at a constant value, and their levels vary between 240 and 540 mOsmol kg À1 based on species. The results were at par with the observation of Galagarza et al (2017), who recorded an osmolality in the range of 251.8 to 327.9 mOsmol kg À1 in P. hypophthalmus reared in a recirculating aquaculture system.…”
Section: Osmoregulatory Parameterssupporting
confidence: 79%
“…Varsamos et al (2005) reported that the osmolality in fish is not regulated at a constant value, and their levels vary between 240 and 540 mOsmol kg À1 based on species. The results were at par with the observation of Galagarza et al (2017), who recorded an osmolality in the range of 251.8 to 327.9 mOsmol kg À1 in P. hypophthalmus reared in a recirculating aquaculture system.…”
Section: Osmoregulatory Parameterssupporting
confidence: 79%
“…Plasma biochemistry reference intervals are routinely used in human and veterinary medicine to provide diagnostic information concerning the health status of the subject (94) . approached levels within those reported in Seriola spp.…”
Section: Plasma Biochemistrymentioning
confidence: 99%
“…Plasma biochemistry reference intervals are routinely used in human and veterinary medicine to provide diagnostic information concerning the health status of the subject (94) . Reference intervals are generally not well established for fish, and although there are no official reference intervals established for Seriola spp., various studies on Seriola spp.…”
Section: Plasma Biochemistrymentioning
confidence: 99%
“…The small agranular lymphocytes showed the highest proportion in of S. javus as reported in other species (Modra et al, 1998). This blood cell plays an important role in the immune response and the biological defense system (Galagarza et al, 2017;Singh and Tandon, 2009) by producing antibodies and chemical substances that serve as a defense against the pathogen and parasite infections (Jalali et al 2009;Musa et al, 2013). However, little data has been available for lymphocytes used for a monitoring purpose.…”
Section: Discussionmentioning
confidence: 97%